Highly efficient CO2 conversion on a robust metal-organic framework Cu(I)-MFU-4l: Prediction and mechanistic understanding from DFT calculations. (September 2022) - Yang, Kuiwei; Jiang, Jianwen
Abstract: As a bioinspired metal-organic framework (MOF) with a unique trigonal pyramidal Cu(I) site in a bowl-shaped pocket, Cu(I)-MFU-4 l has emerged as an advanced single-site heterogeneous catalyst for several important reactions. Herein, we computationally investigate Cu(I)-MFU-4 l combining with tetrabutylammonium bromide (TBAB) as a high-performance catalyst for CO2 conversion with propylene oxide (PO) into propylene carbonate (PC), a reaction of great significance in achieving carbon neutrality and sustainable development. Four paths are proposed depending on the initial activation of either PO or CO2 by Cu(I), as well as the ring-opening of PO at Cα -O bond or Cβ -O bond. Density functional theory calculations over a large cluster model reveal that Cu(I) is prone to interact with PO first and the most favorable path (Path 3) involves the sequential ring-opening of PO at Cβ -O bond, CO2 insertion and ring closure with Gibbs energy barriers of 8.0, 2.8 and 10.3 kcal/mol, respectively. In view of such low energy barriers, Cu(I)-MFU-4 l /TBAB is predicted to be highly active for CO2 cycloaddition with PO at ambient conditions. Significant confinement effect is demonstrated in Cu(I)-MFU-4 l by comparing Path 3 over both large and small cluster models. The observed confinement not only stabilizes the intermediates and transition states thermodynamically, but also promotes the ring-opening of PO kinetically, which is mainly attributed to the van der Waals (vdW) interactions between reactive fragments and surrounding frameworks through non-covalent interaction (NCI) analysis. A mechanism of electronic effect competing with steric effect is proposed to rationalize the regioselectivity of ring-opening of PO under different scenarios via natural bond orbital (NBO) charge and NCI analysis. Our results also suggest that Cu(I)-MFU-4 l /TBAB outperforms Cu(II) paddle-wheel MOFs/TBAB reported previously for CO2 cycloaddition with PO. The structural robustness, the soft electron-rich Cu(I) site and the inherent confinement promote Cu(I)-MFU-4 l to be an appealing candidate catalyst for a wide range of reactions. Graphical Abstract: ga1 Highlights: Cu(I)-MFU-4 l /TBAB is computationally predicted to be highly active for CO2 cycloaddition under ambient conditions. Significant confinement is demonstrated and the importance of the environment beyond active site is highlighted. Electronic effect competes with steric effect to dominate the regioselectivity of ring-opening of epoxides. Cu(I)-MFU-4 l /TBAB outperforms Cu(II) paddle-wheel MOFs/TBAB for CO2 cycloaddition with propylene oxide.